(Ton)silly seasons? Do atmospheric conditions actually affect post-tonsillectomy secondary haemorrhage rates?. Issue 7 (5th June 2015) - Cadd, B; Rogers, M; Patel, H; Crossland, G
Abstract: Background: Tonsillectomy is a common procedure, with potentially life-threatening complications. Previous investigations into post-tonsillectomy secondary haemorrhage rates suggest an influence of climactic and atmospheric conditions on haemorrhage rate, particularly temperature and water vapour pressure. With a single emergency department and a large variance in atmospheric conditions, Darwin, Australia, is ideal for investigating the effects of local climate on rates of post-operative haemorrhage. Methods: A five-year retrospective review was conducted of all tonsillectomy procedures performed between 2008 and 2013. Effects of atmospheric variables were examined using Pearson's correlation coefficient and analysis of variance. Results: A total of 941 patients underwent tonsillectomy in the study period. The bleeding rate was 7.7 per cent. No variation was found between wet and dry season tonsillectomies ( p = 0.4). Temperature ( p = 0.74), water vapour pressure ( p = 0.94) and humidity ( p = 0.66) had no effect on bleeding. Conclusion: The findings revealed no correlation between humidity, season, water vapour pressure and haemorrhage rates. Further research should use multi-site data to investigate the effect of air conditioning, humidification and climactic conditions between different regions in Australia.